Popularitas Nukhbatul Fikar dalam Tradisi Studi Hadis Turki 'Uthmānī - Amiruddin, Muh (Department of Qur'an dan Hadith Faculty of Ushuluddin and Philosophy UIN Sunan Ampel Surabaya, 2023)
This article delves into the ascendancy of Nukhbat al-Fikar within the realm of Hadith scholarship during the Ottoman era. It posits that the book’s rise to authority was intricately tied to the establishment of Islamic madrasas under Ottoman rule, an influence stemming from educational practices in Egypt and its environs. Through a comprehensive exploration of Turkish sources, this paper contends that Nukhbat al-Fikar held a prominent place in Ottoman madrasa curricula due to the genealogical connections between Ottoman Hadith scholars and Ibn Hajar al-‘Asqalānī. Additionally, the work’s author, Ibn Hajar al-‘Asqalānī, enjoyed a lofty reputation among Ottoman scholars, which further solidifying the book’s status. This study underscores the popularity of Nukhbat al-Fikar by examining the proliferation of works by Ottoman Hadith scholars. These scholars sought to amplify its impact through translations, commentary notes (ta’līq), comprehensive explanations (sharh), and concise summaries. In doing so, they contributed to the enduring legacy of Nukhbat al-Fikar within Ottoman scholarly and educational circles. This research sheds light on the intricate interplay between educational systems, scholarly authority, and the dissemination of Islamic knowledge in the context of Ottoman Turkey